RSPO2 gene rearrangement: a powerful driver of β-catenin activation in liver tumours. Issue 7 (2nd February 2019) - Longerich, Thomas; Endris, Volker; Neumann, Olaf; Rempel, Eugen; Kirchner, Martina; Abadi, Zahra; Uhrig, Sebastian; Kriegsmann, Mark; Weiss, Karl Heinz; Breuhahn, Kai; Mehrabi, Arianeb; Weber, Tim Frederik; et al.
Abstract : Objective: We aimed at the identification of genetic alterations that may functionally substitute for CTNNB1 mutation in ß-catenin-activated hepatocellular adenomas (HCAs) and hepatocellular carcinoma (HCC). Design: Large cohorts of HCA (n=185) and HCC (n=468) were classified using immunohistochemistry. The mutational status of the CTNNB1 gene was determined in ß-catenin-activated HCA (b-HCA) and HCC with at least moderate nuclear CTNNB1 accumulation. Ultra-deep sequencing was used to characterise CTNNB1 wild-type and ß-catenin-activated HCA and HCC. Expression profiling of HCA subtypes was performed. Results: A roof plate-specific spondin 2 (RSPO2) gene rearrangement resulting from a 46.4 kb microdeletion on chromosome 8q23.1 was detected as a new morphomolecular driver of β-catenin-activated HCA. RSPO2 fusion positive HCA displayed upregulation of RSPO2 protein, nuclear accumulation of β-catenin and transcriptional activation of β-catenin-target genes indicating activation of Wingless-Type MMTV Integration Site Family (WNT) signalling. Architectural and cytological atypia as well as interstitial invasion indicated malignant transformation in one of the RSPO2 rearranged b-HCAs. The RSPO2 gene rearrangement was also observed in three β-catenin-activated HCCs developing in context of chronic liver disease. Mutations of the human telomerase reverse transcriptase promoter—known to drive malignant transformation of CTNNB1 -mutated HCA—seem to be dispensable for RSPO2 rearranged HCA and HCC. Conclusion: The RSPO2 gene rearrangement leads to oncogenic activation of the WNT signalling pathway in HCA and HCC, represents an alternative mechanism for the development of b-HCA and may drive malignant transformation without additional TERT promoter mutation.